Avaliação das atividades antimicrobiana e citotóxica de peptídeos derivados do veneno do anuro Pithecopus megacephalus e da peçonha da aranha Lycosa erythrognatha - Joaquim Teixeira de Avelar Júnior (2019)
Bioactive peptides are a vast class of molecules with diverse biopharmaceutical potentials, including antimicrobial activity over a broad organism classes such as bacteria, fungi, protozoa and viruses. Several of these peptides have also shown antitumoral activity. In this thesis we focused on Pithecopus megacephalus frog secretion, as well as the peptide LyeTx I-Des-His, a synthetic variation of LyeTx I, a peptide purified from the venom of the spider Lycosa erythrognatha, with the objective to find bioactive peptides mainly against cancer cells, more specifically of the triple negative type. The fractionation of the P. megacephala secretion showed a rich variability on peptides and 14 of them were sequenced. From this set, three peptides were synthesized and tested against bacteria, fungi and three cancer cell lines (MDA-MB-231, MCF-7, both from breast cancer and HCT-116 from colorectal cancer) and one non-cancer cell line (HEK- 293), as a control. The results suggested an increase on proliferative activity of two peptides over cancer cells, without apparent activity on HEK-293 cells. In a second part of this work, we proposed to test LyeTx I-Des-His combined with cisplatin, in three different molar proportions. The proportion peptide:cisplatin, (P:C) 1:1, in the IC50 dose, showed synergistic effect as well as a selectivity index value, greater than cisplatin isolated treatment. When investigating the possible cell death mechanisms involved, we observed several indications of autophagic cell death process. This mechanism was supported by the following results: cells treated with P:C combinations arrested in G2/M cell cycle phase, cells were marked in red with the pH sensitive dye acridine orange and when pretreated with an autophagy inhibitor (Bafilomycin A1) this coloration was reversed. In addition, western blot experiments indicated a possible reduction of P21 expression and of AKT phosphorylation. The decreasing of AKT phosphorylation could be indicative of autophagy, as already described. However, other studies are necessary to better clarify the involved pathways on these activities of the drugs. In addition, toxicity studies are essential in a possible validation of LyeTx I-DesHis as a therapeutic drug candidate These findings demonstrated that the peptide LyeTx I-Des-His seems a good candidate to be combined with some well-established drugs, improving the combat to cancer cells, by inducing other death cascades.